ID 154 – Post exercise decrement in CMAP amplitude and myotonia in Hyperkaliemic Periodic Paralysis. Issue 3 (March 2016) - García, B.; León, A.; Banea, O.; Pascual, J.
Abstract : Objective: We describe a patient with presumptive diagnosis of Hyperkaliemic Periodic Paralysis (HPP) triggered by spironolactone and alcohol intake. Short, long exercise tests (LET) and electromyography were performed. Methods and results: A 54-year-old Philippine man with alcoholic hepatopathy and episodes of paralysis was admitted because of ascitic decompensation. He was treated with spironolactone and developed progressive weakness and areflexia. Later, proximal paralysis, high potassium and creatinine kinase levels were observed. An electromyography showed a mild polyneuropathy, myotonic discharges and myopathy. LET demonstrated a decrement of 30% of CMAP amplitude 33 min after exercise. These findings supported the diagnosis of HPP with myotonia. Spinorolactone was removed and paralysis improved in a few hours. Potassium levels normalized. Conclusion: HPP may be suspected in the presence of flaccid paralysis, myotonia and high potassium levels. LET and EMG are useful tools in the diagnosis. Key message: Neurophysiological tests are essential for diagnosis of muscle channelopathies.